An analysis of liquidity skewness for European sovereign bond markets - Vigne, Samuel; Yan, Wei; Hamill, Philip; Li, Youwei; Waterworth, James (My University, 2018)
We examine liquidity skewness by providing an analysis of bid-ask spreads for a comprehensive high-frequency dataset comprising Eurozone countries’ sovereign bonds. European sovereign bond markets exhibited increasing positive skewness over the sample period which was most extreme for Greece, Ireland and Portugal. We argue that positive skewness reflects decreased liquidity during volatile periods. We also report negative skewness in 2007. This can be explained by a feature of the limit-order book rubric of the MTS market where market-makers can submit limit-orders that are more competitive than the current best-price to reduce unwanted inventory without having to execute a market-order.
PUBLISHED
Keywords: Liquidity; Skewness; Bid-ask spread; Sovereign bonds